Laringalização no português brasileiro: uma análise em torno do fenômeno laríngeo e implicações para a comparação de locutor - Oliveira, Julio Cesar Cavalcanti de (2017)
This study investigates the occurrence of laryngalization in Brazilian Portuguese, assessing its status as a relevant prosodic clue in the speaker comparison task, while considering the influences of sex, segment type and prosodic structure. We evaluate how variations in the production of the phenomenon related to different segments, such as consonantal, vowel and total laryngalization rates, could provide evidence about the locutional profile of different speakers. It is also intended to analyze how phonetic-acoustic parameters are related to its occurrence, in order to allow an objective characterization. The analysis developed is based on a semiautomatic method, following a criterion that considers the perception, manual inspection and the analysis of the speech signal, however, the use of specific scripts guaranteed greater automation in the task of prosodic segmentation and extraction of the measures of interest. The analysis of the semi-spontaneous speech of ten subjects, five men and five women, revealed the distinctive potential of the phenomenon for the differentiation of speaking styles, through consistent variations in the vowel laryngalization and total laryngalization rates. It was also found higher rates of the phenomenon concerning to the female group in comparison to the male group, which proved to be a significant result. Among the analyzed parameters, the percentage of the decrease in intensity between modal and laryngeal events was the parameter most modified. The verification of the laryngalization contexts allowed us to prove the role of the prosodic structure as a motivator of the laryngeal phenomenon, indicating a link between laryngalization and demarcation of prosodic boundaries in Brazilian Portuguese.